2006
DOI: 10.1111/j.1464-5491.2006.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term suppression of plasma free fatty acids fails to improve insulin sensitivity when intramyocellular lipid is elevated

Abstract: Plasma FFAs appear to exert no immediate effect on insulin sensitivity/glucose tolerance independent of their action on intracellular lipid moieties. Further research is required to elucidate the duration of FFA suppression required to restore insulin sensitivity following lipid-induced insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previously, Busetto et al [34] have noted a reduction in liver size 8 weeks after gastric banding; hepatic lipid Table 3). IMCL lipid content correlates with insulin sensitivity [35], and short-term starvation is associated with IMCL accumulation [36,37]. No reduction in IMCL lipid during weight loss on hypocaloric diet was observed [24], and likewise, no lowering of soleus muscle fat was found in type 2 diabetes after weight reduction [27].…”
Section: Discussionmentioning
confidence: 94%
“…Previously, Busetto et al [34] have noted a reduction in liver size 8 weeks after gastric banding; hepatic lipid Table 3). IMCL lipid content correlates with insulin sensitivity [35], and short-term starvation is associated with IMCL accumulation [36,37]. No reduction in IMCL lipid during weight loss on hypocaloric diet was observed [24], and likewise, no lowering of soleus muscle fat was found in type 2 diabetes after weight reduction [27].…”
Section: Discussionmentioning
confidence: 94%
“…Four of the six studies assessing the vastus lateralis muscle found a significant increase of IMF after a high-fat diet intervention ( 9 , 20 , 35 , 39 ). These studies implemented a 54–83% fat diet in their experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The use of circulating NEFA as a biomarker is limited by evidence suggesting that plasma NEFA sampled downstream from the site of NEFA uptake does not necessarily predict intracellular NEFA accumulation. Clinical experiments have shown that excessive plasma NEFAs are not required for hypertriglyceridemia to provoke insulin resistance (33), and suppressing NEFA does not reverse insulin resistance when intracellular fatty acids remain elevated (34).…”
Section: Discussionmentioning
confidence: 99%